Pengaruh Motivasi terhadap Hubungan Kejelasan Sasaran Anggaran dan Partisipasi Penyusunan Anggaran dengan Akuntabilitas Kinerja Instansi Pemerintah - Ehrmann Suhartono (Jurnal Akuntansi dan Bisnis, 2006)
This study tries to understand and prove the influences of (1) local government budget goal clarity and local government budget participation on local government institution’s performance accountability (2) motivation on the relation of budget goal clarity and budget participation as well as local government institution’s performance accountability. The subjects of this study are 148 middle and lower managers in local government institutions including section heads/department heads/sub-section head in governmental institutions under the municipality and regencies in the Special Provinces of Yogyakarta. The results show that budget goal clarity and budget participation influence local government institution’s performance accountability. Then motivation acts as moderating variable in the relation of local government budget goal clarity and local government budget participation with local government institution’s performance accountability.